2010
DOI: 10.14236/jhi.v18i2.758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new short generic measure of health status: howRu

Abstract: Background Quality of life is paramount for patients and clinicians, but existing measures of health were not developed for routine use. Objectives This paper describes the development and testing of a new generic tool for measuring health related quality of life (HRQoL) with direct comparison to the SF-12 Health Survey. Methods The new tool (howRu) has four items (discomfort, distress, disability and dependence), rated using four levels (none, a little, quite a lot and extreme), providing 256 possible states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 36 publications
0
62
1
Order By: Relevance
“…We asked teams if and how they assessed outcomes, and requested copies of documentation that was used. The teams described several tools they used for measuring 'outcomes' which were primarily physical, cognitive or emotional status measures, such as the Mini-Mental State Examination 87 or the Timed Up and Go, 88 or generic health outcome measures, such as the HowRU 89 and the European Quality of Life-5 Dimensions (EQ-5D). 90 This illustrates NRTs' everyday operational understanding and use of outcome assessment in practice.…”
Section: Profiles and Processesmentioning
confidence: 99%
“…We asked teams if and how they assessed outcomes, and requested copies of documentation that was used. The teams described several tools they used for measuring 'outcomes' which were primarily physical, cognitive or emotional status measures, such as the Mini-Mental State Examination 87 or the Timed Up and Go, 88 or generic health outcome measures, such as the HowRU 89 and the European Quality of Life-5 Dimensions (EQ-5D). 90 This illustrates NRTs' everyday operational understanding and use of outcome assessment in practice.…”
Section: Profiles and Processesmentioning
confidence: 99%
“…The howRU is a short generic measure of health related quality of life that measures how the patient is feeling physically and mentally, and how much they can do in terms of function and independence. It was designed with electronic data collection in mind and has been validated against the Short form-12 (SF-12) (Ware et al, 1996) score at the aggregate level (Benson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At final review at 16 months (21 months following the initial injury) the patient was cycling regularly and reported further improvements in his symptoms. The OKS at this time was 37/48 with a howRU score of 10/12 (Benson et al, 2010). Table 1 Oxford knee score (OKS) (Dawson et al, 1998) and howRU (Benson et al, 2010) recorded over a 24-month period from the initial consultation 0 24 50 --3 27 56 --6 32 67 11 92 9 37 77 10 83 12 40 83 11 92 15 37 77 10 83 18 41 85 12 100 21 47 98 12 100 24 48 100 12 100 The patient was encouraged to monitor his clinical outcome scores beyond this final review and at 24 months the OKS was 48/48 and the howRU score 12/12.…”
Section: Case Reportmentioning
confidence: 96%
“…[12][13][14] The howRU score is a generic wellbeing score, validated against the SF-12 ® (Short Form 12-item health survey) score, that rates four items ('pain and discomfort', 'feeling low or worried', 'limited in what you can do' and 'requiring help from others') to provide a score from 0 (low wellbeing) to 12 (high wellbeing). 13 Patient demographic details revealed that the overall mean age was 57 years (with no significant age difference between the groups) and that 75% of patients in the study had access to the internet (Table 1). All patients received a leaflet in clinic, encouraging them to register a score and read additional information (provided by NHS Choices) about their condition on the web-based system.…”
Section: Methodsmentioning
confidence: 99%